Characteristics of diffusion tensor imaging of central nervous system in children with tourette's disease. Issue 22 (29th May 2020) - Xia, Xianwu; Lin, Yeqing; Lang, Boxu; Yuan, Jianjun; Sheng, Liang; Yang, Dengfa; Shen, Jianmin
Abstract : Abstract: To investigate the characteristics of diffusion tensor imaging (DTI) of the central nervous system in children with Tourette syndrome (TS). Fifteen children with TS (TS group) and 15 normal children (control group) were studied, and all of them underwent DTI. The apparent diffusion coefficient (ADC) and fractional anisotropy (FA) parameters were calculated using the DTIStudio software. The region of interest was delineated manually. The ADC and FA values of the bilateral caudate nucleus, bilateral globus pallidus, bilateral putamen, bilateral thalamus, and bilateral frontal lobe white matter were measured using the region of interest editor software. The differences of FA values and ADC values between the same brain areas were compared. The associations between ADC, FA values and Yale Global Tic Severity Scale (YGTSS) scores were evaluated by Pearson correlation analyses. The FA values of left globus pallidus and left thalamus were significantly lower in the TS group than in the control group ( P < .05), while the ADC values of the right caudate nucleus and bilateral thalamus were significantly higher in the TS group than in the control group ( P < .05). The decrease in FA in the left thalamus significantly correlated with the YGTSS score ( r = 0.692; P < .05). No correlation was found between FA and ADC values in other brain regions and the YGTSS score ( P > .05). After the DTI analyses, abnormalities were found in the left globus pallidus, right caudate nucleus, and bilateral thalamus in children with TS. Especially the changes in the left thalamus structure was crucial in the pathophysiological clock of TS.